Pengaruh Latihan Senam Aerobik Menggunakan Beberapa Alat terhadap Pencegahan Obesitas Penyebab Diabetes dan Pengaturan Kadar Glukosa Darah pada Pria Usia 35-45 Tahun - Haider, Hasan (Indonesia Sport Journal, 2025)
The research problem is that diabetes has become one of the so-called diseases of our time and one of the most widespread chronic diseases in Iraq. According to estimates by Iraqi health professionals, diabetes has multiple causes, the most important of which is obesity, which causes diabetes. It is well known that losing weight is difficult for non-athletic individuals. Therefore, the researcher's goal was to develop aerobic exercises to prevent obesity and regulate blood sugar levels, and to determine the effectiveness of these exercises in losing weight, treating obesity, and regulating blood sugar levels. The research sample consisted of (10) males aged 35-45 years. The aerobic exercises developed by the researcher were applied to the sample for (6) weeks, at a rate of three training sessions per week. These exercises were characterized by continuity and gradual progression in intensity and type. The researcher reached the most important conclusions, the most important of which is that practicing aerobic exercises affects weight loss and regulates blood sugar levels for the research sample.